2013
DOI: 10.1007/s00266-012-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Neck-Lifting Procedure: Isolated Stork Lift

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Eleven studies were rated level 2 in quality of evidence . Seven of these (64%) concerned soft-tissue techniques; 2 (18%), tissue sealants; 1 (9.1%), topical use of silicone to prevent scarring; and 1 (9.1%), the use of resurfacing at the time of rhytidectomy .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were rated level 2 in quality of evidence . Seven of these (64%) concerned soft-tissue techniques; 2 (18%), tissue sealants; 1 (9.1%), topical use of silicone to prevent scarring; and 1 (9.1%), the use of resurfacing at the time of rhytidectomy .…”
Section: Resultsmentioning
confidence: 99%
“…The filler is injected in small boluses after proper aspiration. Another new point was the point on mastoid process, 4 its anatomy was studied and no major risk of bolus injection was seen as the occipital branch of the external carotid artery passes behind it 5 …”
Section: Discussionmentioning
confidence: 99%
“…Skin pleating, or lateral skin folds, results from skin laxity as part of the natural aging process. 42 They can also present in a secondary rhytidectomy and neck lift patient due to inadequate excision of neck skin at the time of the primary procedure. It has been reported that utility of a limited incision via the minimal access cranial suspension technique has demonstrated higher rates of neck laxity, neck pleating, and periocular pleating.…”
Section: Neck Skin Pleatsmentioning
confidence: 99%
“…Barbarino et al also discussed the isolated stork lift procedure for correcting vertical and diagonal lateral neck folds and reported 100% correction with high patient satisfaction in the postoperative period. 42…”
Section: Neck Skin Pleatsmentioning
confidence: 99%